2017
DOI: 10.7150/jca.17816
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cytotoxic Activities of the Oral Platinum(IV) Prodrug Oxoplatin and HSP90 Inhibitor Ganetespib against a Panel of Gastric Cancer Cell Lines

Abstract: Gastric cancer exhibits a poor prognosis and is the third most common cause of cancer death worldwide. Chemotherapy of metastatic gastric cancer is based on combinations of platinum drugs and fluoropyrimidines, with added agents. Oxoplatin is a stable oral platinum(IV) prodrug which is converted to a highly active tetrachlorido(IV) complex under acidic conditions. In the present work, we studied the cytotoxic effects of oxoplatin against a panel of four gastric cancer cell lines in vitro. Furthermore, the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Platinum-based agents, such as cisplatin, can also elevate intracellular ROS levels. 37 To evaluate whether ROS production contributed to the cell-killing process of P1-Q1 and P1-Q2 , the intracellular ROS production levels were determined by fluorescence microscopy observation using a DCFH-DA probe. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum-based agents, such as cisplatin, can also elevate intracellular ROS levels. 37 To evaluate whether ROS production contributed to the cell-killing process of P1-Q1 and P1-Q2 , the intracellular ROS production levels were determined by fluorescence microscopy observation using a DCFH-DA probe. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HSP70/HSP90-organizing protein may protect GC cells from fluorouracil chemotherapy in an autocrine manner [18]. The HSP90 inhibitor synergizes with platinum and regulates the proliferation and invasion of GC cell lines [19]. Increased HSP90 or lysine demethylase 5B can facilitate the recruitment of X-ray repair cross complement 1 to repair DNA damaged by platinum, and inhibition of HSP90 can reverse chemoresistance in GC [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that it inhibits the growth of neoplastic tumors more than cisplatin and may weaken the process of distant metastases [85]. The cytotoxic properties of oxoplatin have been observed in vitro in neoplastic cells of the pancreas, colon, prostate and stomach [85,88]. However, the mechanism of action of this compound has, as yet, not been fully determined.…”
Section: Oxoplatinmentioning
confidence: 99%